Nanocompósitos de poli(glicerol sebacato) reforçados com nanowhiskers de caroá (Neoglaziovia variegata) e macambira (Bromelia laciniosa) - Macêdo, Murilo José Pereira de (2013)
Natural fibers were studied to investigate possibilities and better treatment techniques for the development of nanocomposites with poly(glycerol sebacate) (PGS). In this study, the potential of plants such as caroá (Neoglaziovia variegata) and macambira (Bromelia laciniosa) was investigated as sources of natural fibers to obtain whiskers by acid hydrolysis. Fibers were obtained from plant leaves of each species were pre-treated with alcohol and water to remove impurities, treated with aqueous sodium hydroxide (mercerization) and then with sodium chlorite (bleaching) before hydrolyzing with sulfuric acid in order to obtain cellulose whiskers. Fibers and whiskers were characterized thermogravimetric analysis (TGA), X-ray diffraction (XRD) and the morphology was analyzed by Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). Polymers and composites reinforced with whiskers were characterized by TGA, DSC, mechanical (tensile) tests and Fourier Transform Infrared Spectroscopy (FTIR). Results show that it was possible to extract whiskers from both natural and macambira and composite properties were dependent on whisker content.